Association between − 308 tumour necrosis factor promoter polymorphism and bronchial hyperreactivity in asthma - LI KAM WA, T. C; MANSUR, A. H; BRITTON, J; WILLIAMS, G; PAVORD, I; RICHARDS, K; CAMPBELL, D. A; MORTON, N; HOLGATE, S. T; MORRISON, J. F. J (Clinical and experimental allergy, 1999)
Background Tumour necrosis factor (TNF) is a pivotal cytokine in the inflammation underlying asthma. The TNF gene is located in the polymorphic HLA class 3 region on chromosome 6p. Several polymorphisms in this region have been described and associated with alteration of TNF secretion in vitro. Objective In this study we tested the hypothesis that two such polymorphisms, lymphotoxin α NcoI B*1 and − 308 TNF2 may be components of the genetic predisposition to asthma. Methods Five hundred and fifty‐six random individuals were studied, comprising approximately equal numbers of asthmatic subjects, with or without atopy, and a nonatopic nonasthmatic control group. In addition, 355 subjects (172 asthmatics) from 60 multiplex families were typed at the LTα NcoI locus. Results There was an association between allele two of the − 308 TNF polymorphism and bronchial hyperreactivity (OR 2.12, 95% CI 1.04–4.32, P = 0.036). However, there was no association with LTα NcoI alleles. To determine whether this was influenced by linkage disequilibrium within the MHC, 91 subjects with bronchial hyperreactivity and 85 control subjects were typed for class 2 and 3 alleles. Following identification of the extended TNF2 haplotype, we found no independent association of these alleles with BHR. Conclusions We conclude that the − 308 TNF2 promoter polymorphism may form a component of the genetic predisposition to BHR in asthma.